MR imaging of the abdomen and pelvis - Hamm, Bernd , Prof. Dr (Thieme, 2010)
A practical guide to abdominopelvic MR Imaging. It provides an overview of MR Imaging of the abdomen and pelvis in adult and pediatric patients. It presents more than 1,000 abdominal and pelvic MR scans. It includes technical developments and summarizes MR imaging findings, differential diagnoses, and imaging protocols in easy-to-read tables.